Fan phenomena. - Frankel, Valerie Estelle, 1980- (Fan phenomena., 2019)
Even as a new generation embraces the Harry Potter novels for the first time, J.K. Rowling's world is expanding with Fantastic Beasts, Cursed Child and Pottermore. There are new mobile games, new toys and, of course, the theme parks. Meanwhile, Quidditch and the Harry Potter Alliance stretch from college to college, inspiring each generation. Fans have adapted the series into roleplaying games, parodies, musicals, films, dances, art and published fiction like Tommy Taylor or Carry On. They are also scrambling Potter with new franchises: Game of Thrones, Hunger Games, Percy Jackson, Hamilton. What else is this new generation discovering about loving Potter? Which are the best conventions, the best fanfiction and wizard rock? And, how has Potter aged and what does it still have to teach us? Fan Phenomena: Harry Potter offers Potter fans a taste of the best the fandom has to offer.